The Effect Of Impaired Loan And CAR To Banking Performance At Private National Bank : Listed On Indonesia Stock Exchange 2015-2019 - Ratnawati, Aryanti; Susanto, Bambang; Saepudin, Saepudin; Herdiyanti, Gita; Rudianto, Dudi; Khalingga, M Ariq (Adpebi International Journal of Multidisciplinary Sciences, 2022)
The purpose of this study was to determine the effect of impaired loans and capital adequacy ratios on banking performance at Private Commercial Banks listed on Indonesia Stock Exchange for period 2015-2019. Research method uses a quantitative approach with multiple regression analysis. The source of this research uses secondary data. The sample of this study were 18 companies Private Commercial Banks using purposive sampling technique. Finding test results show that Impaired Loans have no significant effect on banking performance while the Capital Adequacy Ratio has a significant effect on banking performance. Simultaneously, it shows that Impaired Loans and the Capital Adequacy Ratio have a significant effect on banking performance. Value the determination coefficient of 0.075 indicates that the Impaired Loan and the Capital Adequacy Ratio provide a variation of 7.5% on banking performance, while the remaining 92.5% is influenced by other factors that are not observed.